Macroeconomic policy and pro-poor growth in Bolivia - Stephan Klasen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
In this paper, we analyze the potential and limitations of macroeconomic policy to affect propoor growth in Bolivia. After discussing the possibility to use macro policy to affect pro-poor growth in general, I then turn to the case of Bolivia, a highly dualistic small open economy that undertook significant macroeconomic and structural reforms in the 1990s. We show that the growth these reforms generated was generally pro-poor in the 1990s but was not enough to achieve significant poverty reduction due to high levels of initial inequality. It also made the country more vulnerable to external shocks which forced the economy into an anti-poor contraction after 1998. Using a dynamic CGE model we demonstrate that there are only limited options for pro-poor macro policy which is particularly due to the low domestic savings rate and the high rate of dollarization of the economy. Consequently, in order to increase the options for pro-poor macro policy, the large inequality, the high dualism, the low savings rate, and high dollarization of the economy need to be addressed.
Keywords: O1; I32; C68; 330